Assessment of Old Age Behaviors Toward Cardiovascular Health Promotion - Ali, Hawraa; Qassim, Wissam Jabbar (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: To assess old age behaviors toward cardiovascular health promotion, and to find out the association between old age behaviors toward cardiovascular health promotion with certain sociodemographic characteristic and chronic disease and significant differences in old age health promotive behaviors with respect to the type of geriatric home residence. Methodology: A descriptive study is conducted throughout the period from April 12th 2022 to June 1st, 2023, to assess the old age behaviors toward cardiovascular health promotion. A purposive sample of (140) old age were selected from males and female’s participants from public and private Geriatric Homes at Baghdad City. The validity and reliability of the questionnaire was performed. Data statistical analysis was done through the use of the descriptive and inferential statistical parameters by the SPSS program version (26). Results: The study result indicates that the study subjects have fair level of health promotive behaviors related to CVDs at their physical activities, dietary patterns, medications use, psychological and mental wellbeing, and seeking for health care. Demographic data and general health statues among elderly in geriatric homes had an impact upon their health promotive behaviors toward CVDs. Conclusion: The findings indicate that the majority of the elderly studied exhibit fair and reasonable level of CVDs health promotion behaviors. These behaviors demand a significant degree of lifestyle modification and are also difficult. Thus, the elderly cannot totally adhere to such activities. Recommendations: The study recommends for create a courses for small group counselling that will educate elderly about the importance of a healthy behaviors and its relationship with having CVDs. Implementing and bolstering health education programs through establishing joint effort between the Ministry of Labor and Social Affairs and the Ministry of Health in order to improve the CVDs health promotion behaviors of residents of geriatric care facilities.